Ensembling of Stacked Denoise Autoencoder for Phishing Attack Detection - K, Sumathi; V, Sujatha (International Journal of Computer Sciences and Engineering, 2019)
Phishing is one of the most severe threats to internet security. It utilizes spotted websites to rob users’ passwords and online identities. Generally, phishers use spotted emails or instant messages to attract users to phishing websites. In order to detect phishing attacks in the network, Deep Neural Network (DNN) was introduced. However, the computational complexity of DNN-based phishing attack detection is high because of using irrelevant and redundant features in DNN. So, DNN with Stacked Denoise AutoEncoder (DNN-SDAE) was proposed which reconstructed input features by removing irrelevant and redundant features. Then, the softmax activation function was processed the reconstructed features detect the phishing attack. In this paper, DNN with Ensembling SDAE (DNN-ESDAE) is proposed to reduce the complexity of SDAE and enhance the phishing attack detection accuracy. Initially, Uniform Resource Locator (URL)-based features, Hyper-Text Markup Language (HTML)-based features and domain-based features are extracted by using feature extractor. Then, individual type of features is processed in different SDAE which reconstruct input features. After the ensembling of three SDAE using negative correlation learning, the best selective ensembling is chosen using Shuffled Frog Leaping Optimization Algorithm (SFLOA). Finally, majority voting is employed to combine the results of three SDAE. The experiment is conducted to prove the effectiveness of DNN-ESDAE in terms of accuracy, precision, recall, and f-measure.